Analisis Supply Chain dan Lean Thinking Komoditas Selada di BSI Farm Kota Bogor Jawa Barat - Veralianta Sebayang; Angela Ivana; Allieccia Tessalonika Wijaya; Deni Rahman; Ilham Hasrimi; Noviqa Shaumi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Curly Lettuce is a vegetable that has the potential to be developed because it contains many nutrients that the body needs. Consumption of Curly Lettuce continues to increase, triggering competition between supply chains to meet consumer needs. BSI Farm is a business entity in the hydroponic agribusiness sector that markets several types of hydroponic vegetables, especially Curly Lettuce. To determine the condition and efficiency of supply chain marketing, analysis is needed by collecting qualitative and quantitative primary and secondary data. Primary data was obtained from direct observation or observation at the research location and in-depth interviews with supply chain actors. The result of this analysis is that the curly lettuce supply chain is not yet efficient. Next, an analysis was carried out using a Lean Thinking approach to determine the causes of supply chain inefficiency. The final result of the Lean Thinking analysis is an alternative solution, which requires proper coordination and collaboration between supply chain actors and within the internal parts of each supply chain to increase marketing efficiency.